The Li+, Na+ and K+ ion exchange reaction process on the surface of mixed oxide SiO2/TiO2/Sb2O5 surface prepared by the Sol-Gel processing method - Ferreira, Cláudia Urbano; Gonçalves, José Eduardo; Kholin, Yuriy Valentinovych; Gushikem, Yoshitaka (Eclética Química, 2005)
The porous mixed oxide SiO 2 /TiO 2 /Sb 2 O 5 obtained by the sol-gel processing method presented a good ion exchange property and a high exchange capacity towards the Li + , Na + and K + ions. In the H + / M + ion exchange process, the H + / Na + could be described as presenting an ideal character. The ion exchange equilibria of Li + and K + were quantitatively described with the help of the model of fixed tetradentate centers. The results of simulation evidence that for the H + / Li + exchange the usual situation takes place: the affinity of the material to the Li + ions is decreased with increasing the degree of ion exchange. On the contrary, for K + the effects of positive cooperativity, that facilitate the H + / K + exchange, were revealed.